Investigation of mechanical performance of woven kenaf/glass hybrid composite metal laminate - Subramaniam, Kathiravan (2021)
In the past few decades, research and engineering interests have been shifting from monolithic materials to fibre reinforced polymer materials. The biggest advantage of composite materials is that they are lightweight as well as tough. By choosing the suitable combination of matrix and reinforcement, a new material can be produced that meets the requirements of a particular application. In order to improve the properties of existing composites, new research leads to the development of Fibre Metal Laminate (FML). Fibre Metal Laminates (FML) is a class of hybrid structure formed from the combination of thin metal layers and fibre reinforced composites bonded together. The increasing of environmental concerns and the need for high-performance materials lead to the development of natural and synthetic hybrid composites. Hybridization of natural and synthetic fibres in single matrix results in the enhancement of mechanical properties of the composite by taking the best advantages of one fibre to overcome the disadvantage of another fibre which consequently minimize the dependent on synthetic fibres. This work presents the effects of fibre stacking configuration on tensile and quasi-static indentation (QSI) and low-velocity impact (LVI) on kenaf/glass hybrid fibre metal laminates (FML). Two different hybrid stacking configurations of kenaf/glass metal laminates reinforced with polypropylene matrix were prepared through a hot compression process. Non-hybrid kenaf and glass metal laminates were also prepared for comparison. A tensile test was conducted according to ASTM E8, a QSI test was conducted according to ASTM D 6264 using 12.7 mm and 20 mm hemispherical indenters while an LVI test was conducted in accordance with ASTM D 7136. The tensile fractured surface of FML laminates was examined using scanning electron microscopy (SEM) while optical micrograph was used to investigate the failure mechanism of quasi-statically penetrated laminates. From the results, FMLs with the glass plies at the outer layers of composite [G/K₂/G] showed a positive hybrid effect as they displayed better tensile, penetration and impact resistance, compared to the non-hybrid kenaf and glass reinforced FMLs. For tensile test, [G/K₂/G] hybrid FML able to withstand higher strength compared to non-hybrid glass FML composites while for quasi-static indentation (QSI) test, [G/K₂/G] hybrid FML exhibit highest penetration load and energy absorption followed by non-hybrid glass FML [G3], [K₂/G/K₂] and lastly [K6]. Similar behaviour is noticed as QSI, [G/K₂/G] hybrid FML display good impact resistance in overall. It was observed that the overall performance of FML laminates decreases as the kenaf content in laminates increases. The potential of kenaf/glass hybrid FMLs in tolerating impact loads is evident. Thus hybrid structure can be used for impact loading applications while reducing the dependence on synthetic fibres. Overall, this study is an exploration of the potential applications of metal laminates reinforced with natural and synthetic fibre.